Parameningeal alveolar rhabdomyosarcoma in a child. Issue 7 (15th July 2021) - Kumar, Abhinav; Pothula, Vijay
Abstract : This is the case of a parameningeal alveolar rhabdomyosarcoma (ARMS) in a 13-year-old boy who presented with painless loss of vision in the right eye, but very few other physical signs. The ARMS diagnosis was confirmed with imaging and molecular characterisation of the tumour. Despite tolerating the initial chemotherapy and radiotherapy regimens, there was leptomeningeal recurrence and the patient unfortunately passed away. Parameningeal ARMS occurs in an area of the body, which leads to a wide variety of possible presenting symptoms, creating a long list of differentials that can delay treatment. This tumour subtype has a poor prognosis, and due to the location of the tumour around vital structures in the head, treatment toxicities must be taken into account. This highlights the necessity for having a strong index of suspicion for this tumour in atypical presentations in children, and the necessity for prompt treatment to prevent leptomeningeal disease from occurring.